Numerical Simulation And Experimental Investigations On The Effect Of Polypropylene Rheology In The Injection Molding Process - Rusdi, Mohd Syakirin (2014)
The design and fabrication of the mold are costly for the injection molding machine. Prior to the fabrication process, the prior to molding analysis is important to investigate the flowability of molten plastic in the mold design. The pre-molding analysis is carried out using simulation software, with the purpose to reduce the fabrication cost and time. Numerical simulation has been proven as a good tool and cost effective way for pre-molding analysis. Therefore, this research focuses on the unsteady three-dimensional (3D) simulation of mold filling during the thermoplastic injection molding process using ANSYS FLUENT 14 software. Common Polypropylene (PP) and medical grade materials are considered in the study. Commercial single screw injection molding machine (Battenfeld TM750/21 O) is used to study the flow front advancement of the common polypropylene at different injection pressures and melt temperatures ofa single cavity of the tray. GOTfFERT Rheograpb25 Capillary Rheometer machine is employed to perform the experiments on the rheological behavior of the polypropylene (i.e., shear rate and viscosity) at different melt temperatures. The rheological results are compared with those obtained by numerical simulation.